Resource books for teachers : younger learners - Phillips, Sarah (New York : Oxford University Press, 1995)
This popular series addresses the needs of primary teachers, teacher trainers, and trainee teachers.
Includes index.
Keywords: English language -- Foreign speakers. -- Study and teaching (Elementary); Primary schools -- English language -- Curriculum